2022
DOI: 10.1002/ece3.9110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing scale‐dependent effects on Forest biomass productivity based on machine learning

Abstract: Estimating forest above‐ground biomass (AGB) productivity constitutes one of the most fundamental topics in forest ecological research. Based on a 30‐ha permanent field plot in Northeastern China, we modeled AGB productivity as output, and topography, species diversity, stand structure, and a stand density variable as input across a series of area scales using the Random Forest (RF) algorithm. As the grain size increased from 10 to 200 m, we found that the relative importance of explanatory variables that drov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…For example, Chu et al (2020) reported the mean absolute error, mean bias error, mean relative error, mean square error, and RMSE for the proposed hybrid BBI rice prediction model. The aforementioned errors are scale-dependent errors (He et al, 2022) which are calculated and interpreted as the error metrics expressed in the units of the underlying data. Meanwhile, Khaki et al (2020) assessed their CNN-RNN maize yield prediction model based on RMSE and correlation coefficient percentage.…”
Section: Model Performance Comparabilitymentioning
confidence: 99%
“…For example, Chu et al (2020) reported the mean absolute error, mean bias error, mean relative error, mean square error, and RMSE for the proposed hybrid BBI rice prediction model. The aforementioned errors are scale-dependent errors (He et al, 2022) which are calculated and interpreted as the error metrics expressed in the units of the underlying data. Meanwhile, Khaki et al (2020) assessed their CNN-RNN maize yield prediction model based on RMSE and correlation coefficient percentage.…”
Section: Model Performance Comparabilitymentioning
confidence: 99%
“…Parametric models and machine learning methods have been applied to predict forest biomass and carbon density in previous studies. Among them, MLR, M5P, RF, ANN and SVM models are the most widely used with high prediction accuracy [34][35][36]. Therefore, this paper chooses these five models to predict the carbon density of sample plots in Shaoguan city.…”
Section: Prediction Model Of Forest Carbon Densitymentioning
confidence: 99%